2011
DOI: 10.1136/tobaccocontrol-2011-050040
|View full text |Cite
|
Sign up to set email alerts
|

Secondhand smoke levels in public building main entrances: outdoor and indoor PM2.5assessment

Abstract: Indoor locations where smoking is banned are not completely free from SHS with levels similar to those obtained in the immediate entrances (outdoors) where smoking is allowed, indicating that SHS from outdoors settings drifts to adjacent indoors. These results warrant a revision of current smoke-free policies in particular outdoor settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
55
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(66 citation statements)
references
References 17 publications
(27 reference statements)
11
55
0
Order By: Relevance
“…The utility of these preventive measures related to an objective measurement can also be seen in a study that assessed cotinine levels 20. Similar results were reported in another study that measured indoor nicotine concentrations at a non-smoking location and in the space next to the entrances of public buildings 12. Another study established that opening the window to air out the car is not sufficient, considering the particle levels in the air.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…The utility of these preventive measures related to an objective measurement can also be seen in a study that assessed cotinine levels 20. Similar results were reported in another study that measured indoor nicotine concentrations at a non-smoking location and in the space next to the entrances of public buildings 12. Another study established that opening the window to air out the car is not sufficient, considering the particle levels in the air.…”
Section: Discussionsupporting
confidence: 61%
“…Conventional ventilation systems cannot eliminate TSP. Ventilation cannot achieve safe TSP levels in the home or in the car 12 13…”
Section: Introductionmentioning
confidence: 99%
“…It is worth noting that Spain ranks among the countries of highest cigarette consumption in the European Union and in the world (WHO, 2010). High outdoor gas-phase nicotine concentrations were previously measured in Barcelona in summer 2010 between 0.5 and 1.5 µg m −3 (Sureda et al, 2012).…”
Section: Nicotinementioning
confidence: 98%
“…Moreover, a common belief among smokers is that cigarette smoking in outdoor places does not affect indoor places,23 whereas a previous study indicated that SHS from outdoors settings drifts to adjacent indoors spaces 24. However, currently, few studies have evaluated the impact of Spanish smoke-free legislations in SHS exposure at home25 26 and there is a lack of information in Spain, to the best of our knowledge, on the impact of the smoke-free laws in the adoption of smoke-free homes (SFHs).…”
Section: Introductionmentioning
confidence: 97%